Ventures in Visionary Marketing: Identifying Game-Changing Branding Strategies in NCAA FBS Athletic Departments - Coyte Gene Cooper (Journal of Applied Sports Management, 2015)
In today's competitive entertainment environment, National Collegiate Athletic Association (NCAA) athletic departments are being faced with unique challenges when it comes to attendance figures and fan engagement. To counter these chal-lenges, athletic departments are being forced to come up with strategies to build their brand with consumers. Thus, the purpose of the current research was to sur-vey marketing staff members at NCAA Division I athletic departments ( N = 46) to identify the peer departments considered as visionary in the area of branding. Overall, the research illustrated that In-Game Experience was determined as the most important area for maximizing efficiency in marketing. In addition, specific athletic departments were mentioned for their visionary approach in key areas, and the specific justifications for their success is explored.
Keywords: branding; game day experience; NCAA; social media; promotions